2021
DOI: 10.2147/ijgm.s294331
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Prediction of Coronary Artery Disease by Multiple Abdominal Fat and Anthropometric Indices: Revisit

Abstract: The aim of this study was to evaluate the efficiency of multiple abdominal fat indices measured by ultrasound and anthropometric indices to predict the presence and severity of coronary artery disease (CAD) assessed by coronary angiography. Patients and Methods: All participants subjected to clinical and laboratory assessments. Anthropometric measurements were taken followed by an ultrasound examination to measure fat thickness at multiple abdominal areas. Lastly, selective coronary angiography performed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…In the present study all these indices were higher in cases than healthy controls as in agreement with these previous studies. Waist hip ratio, waist height ratio and body mass index were positively associated with LDL-C levels which may further contribute to CAD/CHD risk as according to studies (Chitra et al 2012;Wang et al 2018;Hazem et al 2021). Body mass index, waist circumference and waist height ratio are good noninvasive predictors of severity of coronary artery disease risk (Hazem et al 2021) while body adiposity index and body roundness index proved to be best indicators of estimating CHD risk (Wang et al 2018).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study all these indices were higher in cases than healthy controls as in agreement with these previous studies. Waist hip ratio, waist height ratio and body mass index were positively associated with LDL-C levels which may further contribute to CAD/CHD risk as according to studies (Chitra et al 2012;Wang et al 2018;Hazem et al 2021). Body mass index, waist circumference and waist height ratio are good noninvasive predictors of severity of coronary artery disease risk (Hazem et al 2021) while body adiposity index and body roundness index proved to be best indicators of estimating CHD risk (Wang et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Waist hip ratio, waist height ratio and body mass index were positively associated with LDL-C levels which may further contribute to CAD/CHD risk as according to studies (Chitra et al 2012;Wang et al 2018;Hazem et al 2021). Body mass index, waist circumference and waist height ratio are good noninvasive predictors of severity of coronary artery disease risk (Hazem et al 2021) while body adiposity index and body roundness index proved to be best indicators of estimating CHD risk (Wang et al 2018). To the best of our knowledge, no studies have reported the association of total body fat mass and body roundness index with LDL-C and atherogenic index.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Além disso, conforme Hazem 6 , estudos provaram que a adiposidade visceral desempenha um papel importante no desenvolvimento de doenças e distúrbios relacionados à obesidade mais do que a obesidade geral, sugerindo o importante papel da gordura visceral nas doenças cardiovasculares e metabólicas.…”
Section: Introductionunclassified